Survival Strategy of Traditional Small Retail in Competition with Modern Large Retail - Andi Sri Wahyuni (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
This study aims to understand how traditional small retail businesses in Italy compete with large modern retail businesses. This study is a qualitative case study and utilized direct observation for 145 hours in three regions in Italy”Pescara, Chieti, and the factory area”and then conducted a thematic analysis of their survival strategy. The study find that the main factor that determines the sustainability of tabaccai (a traditional small retail in Italy) is the support of the local government, which is strengthened by the local society and the ability of the owners to adapt to the environment. Government support in the form of providing access to limited public goods is an important element in the survival of traditional small retail. These empirical findings provide a new recommendation for traditional small retail businesses in developed countries on how to survive amid the growth of large modern retail businesses.